Estimation of Cadmium Contamination in Different Restoration Scenarios by RUSLE Model: DOI: 10.32526/ennrj.18.4.2020.36 - Charoenpanyanet, Arisara; Huttagosol, Panlop (Environment and Natural Resources Journal, 2020)
The Mae Tao watershed of Thailand faced cadmium (Cd) contamination problems from zinc mining for a long time until the mining area was closed to decrease the level of Cd concentration. This study reproduced the possible scenarios of Cd contamination due to soil loss. Four scenarios of forest restoration were implemented in this study, all of which were calculated with the Revised Universal Soil Loss Equation (RUSLE) integrated with satellite imagery and Geographic Information Systems (GIS). Landsat 8-OLI was acquired and land use/land cover (LULC) was classified in each scenario. Soil loss maps were created. An inverse distance weighting (IDW) technique was used to estimate the concentration of Cd based on the field data consisting of 101 points of measured Cd concentration. Results from RUSLE model and IDW technique were combined to calculate Cd contamination due to soil loss for all four scenarios. Results showed that the restoration of Scenario 3, forest restoration in old and new mining areas in cooperation with reservoir construction, helped decrease Cd contamination the most. The lowest level of Cd contamination from soil loss was found in this scenario by about 156 ha (total of Cd contamination by 165,924.32 ton/year).